Circulating and tumor myeloid-derived suppressor cells in resectable non-small cell lung cancer - Yamauchi, Yoshikane; Safi, Seyer; Warth, Arne; Eichhorn, Martin E.; Herth, Felix; Platten, Michael; Utikal, Jochen; Hoffmann, Hans; Umansky, Viktor (American journal of respiratory and critical care medicine, 2018)
Rationale: Myeloid-derived suppressor cell (MDSC) expansion has been found to play a role in disease progression in patients with cancer. However, the characteristics of MDSCs in lung cancer are poorly understood.Objectives: We prospectively investigated MDSCs and inflammatory factors in tumor and peripheral blood samples from patients with resectable non-small cell lung cancer and studied their correlations with the disease prognosis.Methods: A complex analysis of MDSC subsets and inflammatory mediators was performed using flow cytometry and a Bio-Plex assay.Measurements and Main Results: A significant increase in the frequency of circulating monocytic (M)-MDSCs was observed in the patients with non-small cell lung cancer compared with the healthy donors (HDs). Moreover, the frequencies of M- and polymorphonuclear (PMN)-MDSCs were higher in tumors than in the peripheral blood of the same patients. This accumulation was associated with elevated concentrations of inflammatory mediators involved in MDSC migration to and activation in the tumor microenvironment. An analysis of the MDSC immunosuppressive pattern showed increased programmed death-ligand 1 expression on circulating cells from patients compared with HDs. Tumor PMN-MDSCs displayed higher programmed death-ligand 1 expression levels than the same cells in the peripheral blood. The frequency of CCR5 (C-C chemokine receptor 5) expression on circulating M-MDSCs was significantly higher in the patients than in the HDs. Clinical data analysis revealed negative correlations between recurrence-free survival and the frequencies of PMN-MDSCs and CCR5+ M-MDSCs in the circulation but not in tumors.Conclusions: Our findings suggest that the level of MDSCs in the peripheral blood but not in tumor tissues predicts recurrence after surgery.